(untitled) (The Dhaka University Journal of Earth and Environmental Sciences, 2025)
The present research aims to investigate the coping mechanisms adopted by local residents in the haor region of Bangladesh in response to poverty and flooding. The study was conducted in Galgali Mallikpur village of Mohonganj Upazila, Netrokona and employed observations, FGDs, household questionnaire surveys, and KIIs to collect data from the field. Mallikpur village is frequently flooded during the rainy season, impacting virtually all dwellings (95 percent). 43.2 percent of the households in this village use sandbags to protect their homes against floods, while 20.1 percent use a local bamboo fence, and 17.3 percent raise the level of their homesteads. Seasonal migration (43.2 percent), loans (82.7 percent), and alternative economic sources (29 percent) are the coping and mitigation strategies taken by the families to deal with flood induced poverty. However, these initiatives do not assist Mallikpur inhabitants break the cycle of poverty: 93.75 percent of the population lives below the poverty line and has limited access to healthcare and education. The Dhaka University Journal of Earth and Environmental Sciences, Vol. 13(2), 2024, P 49-62